Management of a large delayed esophageal perforation in a fresh liver transplant patient with endoscopic placement of a nasopleural drainage tube—a case report. Issue 9 (30th September 2020) - Seth, Rashmi; Dubrovsky, Genia; Busuttil, Ronald W; Cameron, Robert B
Abstract: Esophageal perforation in liver transplant recipients is a rare phenomenon. We herein report a case of an esophageal perforation due to Sengstaken–Blakemore tube in a liver-transplant recipient diagnosed 6 weeks post-transplant. A 2.5-cm mid-esophageal perforation communicating with large complex fluid collection in the pleural space was found. During endoscopy, 16Fr Salem Sump nasopleural tube (NP) was placed traversing through esophageal perforation into inferior aspect of the collection. Over the following 4 weeks, NP decompressed the cavity, allowed its closure and the tube was slowly retracted. By the end of 4 weeks, NP was removed with follow-up esophagogram showing no extravasation of contrast and a healed perforation. Hence, the esophageal perforation was successfully treated via this unique nonoperative approach without the need for major surgery. In instances of chronic leak with a stable patient, this nonoperative strategy should be considered even in immunocompromised patients.